OPTIMASI KONSENTRASI INOKULUM BAKTERI HIDROKARBONOKLASTIK PADA BIOREMEDIASI LIMBAH PENGILANGAN MINYAK BUMI DI SUNGAI PAKNING - Syukria Ikhsan Zam (Jurnal Ilmu Lingkungan, 2010)
The purposes of this research were to get the best inoculum concentration and also to identifythe ability of mixed culture of hydrocarbonoclastic bacteria in oil waste degradation. The isolatswere used are Acinetobacter baumannii, Alcaligenes eutrophus, Bacillus sp1., Methylococcuscapsulatus, Bacillus sp2., Morococcus sp., Pseudomonas diminuta, Xanthomonas albilineans,Bacillus cereus and Flavobacterium branchiophiia. Variation of inoculum concentrations were10%, 15%, and 20% (v/v). Observed parameters in optimization were Total Plate Count (TPC)the culture every 24 hour, Total Petroleum Hydrocarbon (TPH) and Chemical Oxygen Demand(COD) examined at the end of the bioremediation period. Best optimization result then analyzedwith GC/MS. Optimization result indicated the best inoculum concentration was 10% with TPHdegradation 61,79% and COD slope 61,75%. It is assumed that the low value of TPHdegradation and COD slope at 15% and 20% inoculum concentration were caused bycompetition inside the bacterial population at that high inoculum concentration. Thecompetition result in low growth and degradation. The chromatogram indicated thathydrocarbon compound from nC9 – nC32 have been degraded by 9,887% – 88,056%. Theconclusions of this research is the best result of bioremediation was obtained concentrationinoculum at 10% mixed culture.